1-Deoxynojirimycin isolated from Bacillus subtilis improves hepatic lipid metabolism and mitochondrial function in high-fat–fed mice. (January 2015) - Do, Hyun Ju; Chung, Ji Hyung; Hwang, Ji Won; Kim, Oh Yoen; Lee, Jae-Yeon; Shin, Min-Jeong
Highlights: DNJ reduced body weight, fat mass, and energy intakes in high fat fed mice. DNJ modulated genes involved in hepatic lipid abnormalities and mitochondrial dysfunction. DNJ administration as a potential therapeutic use in obesity and obesity-related complications. Abstract: The aim of this study was to determine whether 1-deoxynojirimycin (DNJ) isolated from Bacillus subtilis MORI beneficially influences lipid metabolism and mitochondrial function in the liver of mice fed a high-fat diet in addition to the anti-obesity properties of DNJ. Male C57BL/6 mice (n = 29; 5 weeks old) were randomly assigned to three groups: normal control diet (CTL, n = 10), high-fat diet (HF, n = 10), and high-fat diet supplemented with DNJ (DNJ, n = 9). After 12 weeks, the HF group exhibited higher overall weight gain, of the liver, and of various fat pads than the CTL and DNJ groups did. The HF group also showed greater expression of C/EBPα and CD36 mRNA in the liver than that in the CTL and/or DNJ groups. In addition, mRNA expressions of AAC and FAS were lower, while mRNA expression of PGC-1β was higher in the liver of the DNJ group than that of the HF group. The hepatic expression of p-AMPK/AMPK was higher in the DNJ group than in the HF group. This study provides novel insight into the protective effect of DNJ supplementation against obesity-induced hepatic lipid abnormalities and mitochondrial dysfunction.